A study on supercritical water gasification of black liquor conducted in stainless steel and nickel‐chromium‐molybdenum reactors. Issue 10 (9th February 2016) - De Blasio, Cataldo; Lucca, Gaetano; Özdenkci, Karhan; Mulas, Michela; Lundqvist, Kurt; Koskinen, Jukka; Santarelli, Massimo; Westerlund, Tapio; Järvinen, Mika
Abstract: BACKGROUND: This study presents supercritical water gasification (SCWG) as an alternative treatment process for black liquor: investigating the impacts of black liquor constituents, temperature and catalyst. The preliminary experiments include SCWG of sucrose and isoeugenol in stainless steel reactor, as model compounds of sugars and lignin. Then, the experiments of SCWG of black liquor are performed in stainless steel and INCONEL 625 reactors. RESULTS: The results illustrated the impacts of temperature, black liquor constituents and nickel catalyst on the SCWG process. Temperature and the INCONEL reactor promoted gasification efficiency and hot gas efficiency: over 80% hot gas efficiency was reached for black liquor in the INCONEL reactor at 700 °C. Experiments on model compounds have shown that sugars generate more carbon dioxide, while lignin generates more methane. Hydrogen fraction and yield increased with temperature; nevertheless, black liquor generated hydrogen‐rich gas. The INCONEL reactor increased hot gas efficiency despite no significant impact on carbon gasification efficiency: hydrogen is promoted dramatically. In addition, temperature and the INCONEL catalyst reduce tar and char formation as well. CONCLUSIONS: Supercritical water gasification (SCWG) is potentially a suitable treatment for black liquor: it has no evaporation requirement and high hot gas efficiency. This process can be a solution for non‐wood mills and can increase the product spectrum of Kraft mills by operating as a parallel treatment. On the other hand, sulphur balance is to be investigated for integration with Kraft mills together with a detailed feasibility study. © 2015 Society of Chemical Industry